2022
DOI: 10.1097/prs.0000000000009931
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Reconstruction with Retrorectus Self-Adhering Mesh: A Single-Center Long-Term Follow-up

Abstract: In patients undergoing laparotomy, as many as 10% develop ventral hernias, and the risk increases with each additional repair. 1 One of the most important goals of hernia repair is achieving reliable and durable reconstruction. However, hernia repairs have 10-year recurrence rates as high as 54%. 2,3 Using mesh to reinforce each reconstruction during repair has been consistently shown to reduce the risk of recurrence by as much as 50%. [4][5][6] In addition, obtaining musculofascial reapproximation has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Though longer-term data is not available, the principle of approaching mesh in the same way as other permanent implants is warranted. A related study by the same group, which also used the "no-touch" technique investigated outcomes of using permanent self-adhering mesh, found a shorter surgery and length of stay with no differences in surgical-site occurrences or hernia recurrence [29].…”
Section: When To Use Permanent Synthetic Mesh?mentioning
confidence: 98%
“…Though longer-term data is not available, the principle of approaching mesh in the same way as other permanent implants is warranted. A related study by the same group, which also used the "no-touch" technique investigated outcomes of using permanent self-adhering mesh, found a shorter surgery and length of stay with no differences in surgical-site occurrences or hernia recurrence [29].…”
Section: When To Use Permanent Synthetic Mesh?mentioning
confidence: 98%
“…Currently, two main methods are utilized for mesh fixation: suturing and the use of adhesives [ 2 ]. The history of suturing for mesh fixation in AWR can be traced back to the pioneering work of surgeons in the field of hernia repair.…”
Section: Introductionmentioning
confidence: 99%
“…T he authors should be commended on a wellwritten report of their study comparing outcomes of the use of retrorectus self-adhering mesh and transfascially sutured mesh in abdominal wall reconstruction. 1 In their study of 42 patients with at least 12 months of follow-up, Bashian and colleagues reported that use of self-adhering mesh resulted in rates of hernia recurrence and surgical-site occurrence (SSO) similar to those with use of transfascially sutured mesh but with shorter surgery times and lengths of stay.…”
mentioning
confidence: 99%